Śmierć i uroczystości pogrzebowe w zapiskach siedemnastowiecznych przedstawicieli angielskiej klasy średniej - Dudek, Dorota (Acta Universitatis Lodziensis. Folia Historica, 2015)
In this article using diaries and other kind of memoirs written by Samuel Pepys, John Evelyn, Adam Martindale, Sara Savage, John Dunton, Henry Newcome, as well as 17th century ballads and goodly books, I tried to describe customs connected to process of dying. Particularly I wrote about idea of good death, both in religion and more material sphere, mourning and burial ceremony. In the second part of 17th century reflections connected to death were common and popular due to high mortal rank. People wrote their testaments even few times in life, usually before some risky entertainment, like long voyage or, in case of women, child delivery. Unfortunately in many cases even plain testament wasn’t enough to prevent disagreements between family members. We can observe such problems in Samuel Pepys family. We also have to remember that idea of good death was tightly connected with religion issues and many people spent their last moments on meditations, prayers or giving good advices to family members. In that period were also popular different kinds of guidebooks, especially goodly books, in with were described the proper way of life and, especially, of dying. I described some of them and tried to confront ideals from this kind of literaturę with the life of diaries authors. I also described in details the burial ceremony and the funeral banquet.